The situation of the administrative career, guarantors to the contract of the meit in the general command of FFMM (2016)
This research aims at analyzing the actual situation of the Administrative Career regime current system in the Public Administration of the National Defense Ministry- Military Forces General Office Firstly, I put forward a basic conceptualization of the history and regime of administrative career of the country as well as a description in depth and a study of several references. Afterwards, I describe several relevant aspects to approach the core content of this essay: What factors have hindered the participation in the administrative career as a guarantee to take part in the merit contest in the Military Force General Command? Key words: Administrative Career, Merit, Public Contest, Public Administration